Invariant complex structures on tangent and cotangent Lie groups of dimension six - Campoamor Stursberg, Otto Ruttwig (2012)
This paper deals with left invariant complex structures on simply connected Lie groups, the Lie algebra of which is of the type T h = h + V , where is either the adjoint or the coadjoint representation. The main topic is the existence question of complex structures on T h for h a three dimensional real Lie algebra. First it was proposed the study of complex structures J satisfying the constrain Jh = V . Whenever is the adjoint representation this kind of complex structures are associated to non singular derivations of h. This fact derives different kind of applications.